Evaluation of Pedestrian Pathway Design for Accessibility for Disabilities to Support SDGs and Reduce Carbon Emissions - Dinata, Candra; Hidayah, Retna; Triyono, Mochamad Bruri (Proceeding of International Joint Conference on UNESA, 2024)
People with disabilities have the same right to access public spaces as the public in general. One of the crucial elements of the design of urban public spaces is pedestrian paths. This research was conducted on designing pedestrian paths for people with disabilities in the socio-cultural strategic area of Yogyakarta City. The sample taken was from the Kota Baru area along Jalan Suroto. This research uses an observational quantitative descriptive method through field surveys and literature studies with the stages a) segment determination, b) data collection, c) data evaluation, and d) recommendations. This study has divided the pedestrian pathway into 4 segments. The final results were obtained for segment 1 to receive quality II (High), segment 2 to receive quality I (Very High), segment 3 to receive quality II (High), and segment 4 to receive quality I (Very High). From the results of this research, it is hoped that the quality and accessibility of pedestrian pathways can be improved, creating a safer, more comfortable, and inclusive environment for all users. Eventually, this can also reduce the use of private vehicles, thereby decreasing traffic congestion, air pollution, and carbon emissions.